Discovering Host Genes Involved in the Infection by the Tomato Yellow Leaf Curl Virus Complex and in the Establishment of Resistance to the Virus Using Tobacco Rattle Virus-based Post Transcriptional Gene Silencing - Henryk Czosnek; Assaf Eybishtz; Dagan Sade; Rena Gorovits; Iris Sobol; Rodríguez-Bejarano, Eduardo; Rosas-Díaz, Tábata Victoria; Lozano Durán, Rosa (MDPI, 2013)
The development of high-throughput technologies allows for evaluating gene expression at the whole-genome level. Together with proteomic and metabolomic studies, these analyses have resulted in the identification of plant genes whose function or expression is altered as a consequence of pathogen attacks. Members of the Tomato yellow leaf curl virus (TYLCV) complex are among the most important pathogens impairing production of agricultural crops worldwide. To understand how these geminiviruses subjugate plant defenses, and to devise counter-measures, it is essential to identify the host genes affected by infection and to determine their role in susceptible and resistant plants. We have used a reverse genetics approach based on Tobacco rattle virus-induced gene silencing to uncover genes involved in viral infection of susceptible plants, and to identify genes underlying virus resistance. To identify host genes with a role in geminivirus infection, we have engineered a Nicotiana benthamiana line, coined 2IRGFP, which over-expresses GFP upon virus infection. With this system, we have achieved an accurate description of the dynamics of virus replication in space and time. Upon silencing selected N. benthamiana genes previously shown to be related to host response to geminivirus infection, we have identified eighteen genes involved in a wide array of cellular processes. Plant genes involved in geminivirus resistance were studied by comparing two tomato lines: one resistant (R), the other susceptible (S) to the virus. Sixty-nine genes preferentially expressed in R tomatoes were identified by screening cDNA libraries from infected and uninfected R and S genotypes. This review of our results indicates that TRV-VIGS is an exquisite reverse genetics tool that may provide new insights into the molecular mechanisms underlying plant infection and resistance to infection by begomoviruses.
Keywords: Virus fitopatógenos; Geminivirus; VIGS; Tobacco Rattle Virus-based; TYLCV